Measuring the Distinction between the Belief (Faith) of the People of Yunus (PBUH) with the Lack of Faith of Other Folks Based on the Analysis of the Thematic Content of Surah Yunus (PBUH) - Ramin Tayyarinezhad; Ali Safari; Rāshid Tayyarinejad (آموزه‌های قرآنی, 2022)
In the narration of the invitation of folks (people) by the prophets, the praise of the people of Yunus ʿalayhi as-salām (Arabic: یونس, Yūnus; Arabic synonym of Jonas or Jonah) is a fundamental difference and distinction in relation to the blame of other folks. The reason for the belief (faith) of the folk of Yunus in this study has been analyzed by the method of thematic content analysis and the use of the relation of themes in the method of discourse analysis with the thematic classification of the verses of Surah (chapter) Yunus and the expansion of the related thematic reticulated form in other verses. The findings indicate that the folks and people of all prophets, except Prophet Yunus peace be upon him, denied (were deniers, rejecters, repudiators of) the verses of God. The final notice (ultimatum) to the rejecting folks in two ways of warning and reasoning based on quantitative analysis is the dominant approach in Surah Yunus. The qualitative analyzes show that folks and people gradually turned to the position of refutation (denial) during a longitudinal (vertical, linear) correlation (relationship) of descending (Arabic: تَدَلّی, Romanized: tadallī) [descending from the top to the bottom, coming and going down] from a higher (superior) position to a lower position and what made them unbelievable was the acceptance (the adoption) of such a position against religion. The motivating factor of folks to refutation (denial) is an unhealthy social environment that has been influenced by two factors, in the first place of the behavioral pattern and in the next place, the change of mindsets has been formed by activists with intellectual and political authority under the title of Mala’a (Arabic: مَلأ, Exalted chiefs, the Highest Chiefs, the Chiefs on high). The people of Yunus are the only people in whom there is no mention of the existence of such a class, and instead the presence of an advisor scholar is mentioned in the narrations related to this people.